52‐4: Achievement of Blue Phosphorescent Organic Light‐Emitting Diode with High Efficiency, Low Driving Voltage, and Long Lifetime by Exciplex—Triplet Energy Transfer Technology. Issue 1 (May 2016) - Yamada, Yui; Inoue, Hideko; Mitsumori, Satomi; Watabe, Takeyoshi; Ishisone, Takahiro; Hara, Tomoka; Takahashi, Tatsuyoshi; Nakashima, Harue; Seo, Satoshi
Abstract : Efficient energy transfer from an exciplex to a phosphorescent dopant was successfully introduced to a blue phosphorescent organic light‐emitting diode by carefully designing the exciplex and dopant. This energy transfer simultaneously achieved increase in quantum efficiency, decrease in driving voltage, and improvement in lifetime even in blue devices.